Perlindungan Hukum Bagi Korban Tindak Pidana ITE dalam Kasus Penyebaran Konten Pornografi Digital - Putri Ramadhani Rangkuti; Melia Dwi Hasanah; Mirna Syafitri Rahmadani; Nazwa Bunga Rezki Perdana Lubis; Nadia Putri Naya (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
This study uses a qualitative method with a normative legal approach that aims to analyze legal protection for victims of Information and Electronic Transactions (ITE) crimes, especially in cases of the distribution of digital pornographic content. The rampant distribution of pornographic content through digital platforms is a serious threat to the privacy rights and dignity of victims, especially women and children. In the context of law in Indonesia, protection for victims has been regulated in several laws and regulations such as Law Number 19 of 2016 concerning Amendments to the ITE Law and the Criminal Code (KUHP). However, the implementation of this protection still faces various obstacles, includeing weak law enforcement, limited understanding of victims’ rights, and the suboptimal role of witness and victim protection institutions. Through literature studies and analysis of court decisions, this study found that legal protection is still reactive and has not been optimal in preventing and restoring victims’ losses as a whole. Therefore, a more responsive policy reformulation and strengthening of digital literacy are needed as strategic preventive measures.